Medication Adherence among Drug-Resistant Tuberculosis (DR-TB) Patients at Universitas Indonesia Hospital - Harahap, Daimah Wirdatus Sanaun; Andrajati, Retnosari; Sari, Santi Purna; Handayani, Diah (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Drug-resistant tuberculosis (TB-DR) is a deadly disease caused by infectious agents. Indonesia is one of the countries with the highest drug-resistant tuberculosis (TB-DR) rates in the world. The prevalence of tuberculosis cases in Depok City between 2019-2022 showed an increase in cases every year. This study aims to measure the level of adherence of drug-resistant tuberculosis (TB-DR) patients to their treatment using the Eight-Item Morisky Medication Adherence Scale (MMAS-8) questionnaire.Methods: This study is an observational study using a cross-sectional study design, conducted from February 2024 to March 2024 at the University of Indonesia Hospital. Eighty-seven respondents participated in this study. Respondents completed the validated Indonesian version of the MMAS-8 questionnaire after signing informed consent forms.Results: The results of the study showed that 50.6% of respondents had low adherence levels, 47.1% had moderate adherence levels, and 2.3% had high adherence levels. The data was then statistically analyzed using the SPSS version 29 statistical package with Chi-Square analysis, which resulted in a significant correlation (P<0.05) between adherence levels and gender.Conclusion: There was a significant correlation between gender and respondent adherence. More than 50% of drug-resistant tuberculosis (TB-DR) patients at the University of Indonesia Hospital still have low adherence levels to their treatment.